Application of Fermentation Technology Using Catfish Waste and Banana Stems in Muscovy Duck Feed to Strengthen Fitria Farm’s Poultry Farming Business - Dini Widianingrum; Oki Imanudin; Aaf Falahudin; Lussyana Devitri Miranda; Desinta Aulia Purnama; Melly Ramadani; Ahmad Hablie Khalifa (Unram Journal of Community Service, 2026)
Small-scale duck farming operations face challenges posed by high feed costs and low utilization of local organic waste, which has the potential to serve as an alternative feed ingredient. This Student Creativity Program (PKM) aims to apply fermentation technology to catfish waste and banana stems as innovative feed ingredients in duck rations to improve the efficiency of the farming operations at Fitria Farm. Activities were carried out through a participatory approach that included identifying partner needs, formulating rations based on fermented waste, training in fermentation technology, implementing feed administration, and evaluating production performance and business economics. Catfish waste was utilized as a protein source, while banana stems were fermented to improve fiber digestibility and nutrient content. The fermentation process utilized local microorganism bioactivators (MOL) over a specific period to produce feed of higher quality. Implementation results show that the use of fermented feed is able to improve feed palatability, feed conversion efficiency, and body weight gain in entog, as well as reduce feed costs compared to conventional feed. In addition, this activity enhances partners’ knowledge and skills in processing agricultural and fishery waste into economically valuable feed. Conclusion the technology for fermenting catfish waste and banana stems has the potential to serve as a model for sustainable feed innovation that supports the strengthening of local-resource-based duck farming operations.